Applying economic models to estimate local economic benefits of improved coverage of early intervention for psychosis. Issue 6 (10th February 2019) - Campion, Jonathan; Taylor, Matthew J.; McDaid, David; Park, A‐La; Shiers, David
Abstract : Aim: Early Intervention Psychosis Services (EIPS) for people experiencing First Episode Psychosis (FEP) offer important clinical and non‐clinical benefits over standard care. Similarly, intervention for Clinical High Risk for Psychosis state (CHR‐P) can prevent psychosis, ameliorate symptoms and have non‐clinical benefits. This study aimed to estimate associated local economic benefits of FEP and CHR‐P services compared with standard care. Methods: Across four south London boroughs, proportion of annual number of new cases of FEP and CHR‐P seen by early intervention services was estimated. Economic modelling conducted for England's mental health strategy was applied to estimate local economic impacts of current and improved service provision. Results: Across four London boroughs during 2011/2012, proportion of 15‐34 year olds with FEP seen by EIPS was 100.2% assuming 80/100 000 annual incidence whereas proportion with CHR‐P seen by CHR‐P services was 4.1% assuming 200/100 000 annual incidence. Application of economic modelling suggests that provision of EIPS to reach all new FEP cases each year would free up resources of £13.1m over 10 years including £2.0m to National Health Service (NHS) after the first year. Scaling up to reach all new CHR‐P cases each year would free up resources of £19.7m over 10 years with an estimated 10‐year cost of implementation gap for each 1 year cohort of £18.9m. An earlier related briefing resulted in increased funding for EIPS and new CHR‐P services despite overall cuts to mental health services. Conclusions: Estimation of local economic impacts of FEP and CHR‐P services was associated with improved investment in such services.